The Influence of Tax Knowledge, Tax Understanding, Tax Penalties, and Perceived Benefits on the Tax Compliance of MSME Taxpayers - Rantelobo, Alfred Tandirura; Utami, Sri Endar (Public Policy, 2024)
This study examines the impact of tax knowledge, tax understanding, tax penalties, and perceived benefits on the tax compliance of MSME taxpayers. The research was conducted among MSMEs in Kupang City, involving 95 respondents who were selected through purposive samplingThe data were analyzed using instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The application used to address these issues was the Statistical Package for the Social Sciences (SPSS) version 25. The results showed that all independent variables had a significant positive influence on auditor performance. Task complexity moderated the effect of experience on auditor performance but did not moderate the effect of other variables. The study results reveal a positive influence of tax knowledge, tax understanding, tax penalties, and perceived benefits on the tax compliance of MSMEs in reporting their annual tax returns at KPP Pratama Kupang, both partially and simultaneously.